Flash Catalytic Pyrolysis of Polyethylene over (Alumino)silicate Materials. Issue 4 (2nd January 2020) - Klaimy, Sophie; Ciotonea, Carmen; Dhainaut, Jérémy; Royer, Sébastien; Casetta, Mathilde; Duquesne, Sophie; Tricot, Grégory; Lamonier, Jean‐François
Abstract: A series of amorphous and crystalline (alumino)silicate catalysts, with variable acidity, are evaluated for the flash pyrolysis of polyethylene (PE). Catalysts morphology, acidity as well as textural properties are influencing the process of decomposition of PE. Incomplete PE conversion and significant wax formation are obtained under the reaction condition with pure amorphous and MFI‐type silica. Complete conversion, and limited formation of wax, are observed with amorphous and MFI‐type Si−Al containing catalyst. Acidity has a significant influence on the molecule size and nature. Then, the increase of the catalyst acidity leads to the decrease of the molecular weight of pyrolysis products and the increase of the gas and the light liquid fractions. In addition, the acidity increase promotes cyclization reaction, resulting in the increase of the cycled hydrocarbon/aromatic proportion in the liquid fraction. Then, from PE catalytic pyrolysis, up to 25 wt.% of aromatics can be obtained in the liquid fraction with Si/Al ZSM‐5 zeolite, while olefins remain the major fraction with the less acidic amorphous aluminosilicate catalyst. Abstract : Acidity affects ! A series of amorphous and crystalline (alumino)silicate catalysts, with variable acidity, are evaluated for the flash pyrolysis of polyethylene (PE).